The Brazilian state's redistributive role: Changes and persistence at the beginning of the 21st century - Fernando Gaiger Silveira; Theo Ribas Palomo (Institute for Applied Economic Research (ipea), 2023)
This paper examines the evolution of the redistributive role of the State in Brazil at the beginning of the 21st century. For this purpose, we compute the marginal effects of the cash transfers, taxes, and in-kind benefits on inequality using the Lerman-Yitzhaki progressivity index. Our main results are: i) the Brazilian tax system as a whole remains regressive, with heavily regressive indirect taxes and slightly progressive direct taxes; however, ii) the expansion of social spending in this period introduced significant progressive gains, leading to an iii) increase in the redistributive role of the State and to a net reduction in the final income Gini index by 15.9%. We conclude by arguing that further advancements towards a more progressive tax system could be achieved by reducing the weight of indirect taxes and increasing the taxation of the richest.
Keywords: D31; H22; I3; 330; fiscal redistribution; cash transfers; taxation; in-kind benefits; income inequality